1998
DOI: 10.4269/ajtmh.1998.58.763
|View full text |Cite
|
Sign up to set email alerts
|

A target for intervention in Plasmodium falciparum infections.

Abstract: We present a set of simple mathematical models to investigate interactions between malaria parasites and the human immune system and the differentiation of parasites from asexual, pathogenic into sexual, transmissible blood stages. Each model represents a different combination of empirically based hypotheses, and salient behaviors of each fit criteria developed from clinical data. In all models, however, higher gametocyte conversion rates result in lower peak asexual-form densities. Therefore, to the extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…40 This time lag is in agreement with models proposed recently that predict that an optimizing pathogen should delay production of its transmission stages. 41,42 The higher gametocytemia before treatment in CQ-resistant infections in comparison with sensitive ones has already been observed in other studies in Senegal 29,30 and the Solomon Islands. 43 This might be explained by a higher gametocytogenesis as observed in vitro in CQ-resistant parasites; 28 furthermore, Hogh and others observed that patients harboring CQ-resistant parasites were 4.4 times more likely to produce gametocytes as those harboring sensitive ones.…”
Section: Discussionsupporting
confidence: 52%
“…40 This time lag is in agreement with models proposed recently that predict that an optimizing pathogen should delay production of its transmission stages. 41,42 The higher gametocytemia before treatment in CQ-resistant infections in comparison with sensitive ones has already been observed in other studies in Senegal 29,30 and the Solomon Islands. 43 This might be explained by a higher gametocytogenesis as observed in vitro in CQ-resistant parasites; 28 furthermore, Hogh and others observed that patients harboring CQ-resistant parasites were 4.4 times more likely to produce gametocytes as those harboring sensitive ones.…”
Section: Discussionsupporting
confidence: 52%
“…That is, there is a delay between changes in the Pf population and production of corresponding immune effectors. Delays have been used in disease models with an IR in [17], and for malaria in particular in [13,18,19]. However, we are not aware of any reported measurements of IR delay times for Pf.…”
Section: Introductionmentioning
confidence: 88%
“…We do not consider parasite synchronization, which is likely immune-mediated (27), but note that it would probably benefit the host of a P. vivax infection were reticulocyte susceptibility Ͻ48 h. We also do not consider the blood stages transmissible to mosquitoes; their production entails complex trade-offs between density, persistence, pathogenesis, and transmission (28,29), but these should not alter the qualitative conclusions given here. Here, any correlates of the peak infected RBC count would be maximized simply by maximizing R 0 and f 0 ; larger R 0 values also lead more quickly to catastrophic anemia, however, and correlates of the integrated infected RBC count would be maximized by species-specific balances between R 0 and f 0 .…”
Section: Discussionmentioning
confidence: 99%